Process for the production of low temperature resistant paperboard
By using a combination of antifreeze impregnation liquid and cationic starch in paperboard production, along with a gradient drying process, the problem of paperboard embrittlement in cryogenic environments was solved, achieving the effect of maintaining flexibility and burst strength at low temperatures.
Patent Information
- Application Number
- CN202610935495.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-06-26
AI Technical Summary
Existing cardboard is prone to brittleness in cryogenic environments and cannot meet the requirements for cold chain stacking and impact resistance. At low temperatures, free water and bound water in the fiber cell cavities and cell wall gaps of conventional cardboard crystallize and expand, destroying the hydrogen bond forces between fibers and causing structural damage.
By using a combination of antifreeze impregnation solution and cationic starch in a specific ratio, the antifreeze components are allowed to penetrate into the fiber pores through osmotic pressure and capillary action. Combined with a two-stage gradient drying process, ice nucleus formation is inhibited and hydrogen bonding between fibers is enhanced. Mid-wave infrared energy is used for gentle drying to ensure that the antifreeze solutes are uniformly retained inside the fiber.
Maintaining the flexibility and burst strength of cardboard in cryogenic environments meets the load-bearing requirements of cold chain stacking, while avoiding fiber embrittlement and structural damage.
Abstract
Description
Technical Field
[0001] This application relates to the field of paperboard, and more specifically, to a production process for low-temperature resistant paperboard. Background Technology
[0002] With the large-scale development of the fresh frozen food industry, biopharmaceutical cold chain logistics, low-temperature warehousing, and liquid nitrogen quick-freezing processing industry, the demand for cryogenic packaging across the entire supply chain continues to rise. Currently, the temperature range of the entire cold chain packaging process is large. The temperature of conventional low-temperature cold chain warehousing and transportation is concentrated between -20℃ and -30℃, while the temperature of special working conditions such as liquid nitrogen quick-freezing and low-temperature transportation of biological samples can be as low as -40℃ and below. Paper packaging, with its advantages of being recyclable, biodegradable, low-cost, and environmentally friendly, is gradually replacing non-degradable foam and plastic packaging and becoming the mainstream development direction of green packaging in cold chain logistics.
[0003] Currently, most corrugated cardboard and conventional food packaging cardboard on the market are made primarily from virgin wood pulp fibers, combined with starch-based adhesives. This type of cardboard is only suitable for ordinary cold storage packaging environments at room temperature and above 0°C. In cryogenic environments, because plant wood fibers contain a large number of hydrophilic hydroxyl groups, the free and bound water in the fiber cell cavities and cell wall gaps will rapidly crystallize and expand, destroying the hydrogen bond forces between fibers. At the same time, the low temperature environment will freeze the movement of cellulose macromolecular chains, causing the cardboard substrate to change from a flexible material to a brittle material. Under the action of external forces such as stacking pressure, transportation bumps, bending impacts, etc., structural damage problems such as board surface cracking and collapse are likely to occur. It cannot meet the basic usage requirements of cryogenic cold chain packaging stacking load-bearing and long-distance transportation impact resistance, and needs to be improved. Summary of the Invention
[0004] To address the issues of paperboard becoming brittle under cryogenic conditions and failing to meet cold chain stacking and impact resistance requirements, this application provides a production process for low-temperature resistant paperboard.
[0005] The production process for a low-temperature resistant paperboard provided in this application adopts the following technical solution:
[0006] A process for producing low-temperature resistant paperboard includes the following steps:
[0007] S1. Starch pretreatment: Add cationic starch to hot water at 70-80℃, where the mass of the hot water is 10-12 times the mass of the cationic starch. Heat the water in a constant temperature water bath and stir at 250-350 r / min for 15-30 min to gelatinize the starch and obtain a cationic starch paste. Keep the paste warm for later use.
[0008] S2. Pulp modification: Mix softwood pulp and hardwood pulp at a mass ratio of 6:(3-4), dilute with water to a pulp consistency of 3%-4%, beat the pulp to a freeness of 30-40°SR, add cationic starch paste under heat preservation to the pulp, and stir for 10-20 minutes. The amount of cationic starch added is 1.5%-2% of the oven-dry pulp mass.
[0009] S3. Fiber pore loading: Add antifreeze impregnation liquid to the slurry obtained in S2. The amount of antifreeze impregnation liquid added is 5-6 times the weight of the oven-dry slurry. The antifreeze impregnation liquid includes: 4%-6% soluble inorganic salt, 3%-5% small molecule antifreeze protectant, 0.3%-0.5% penetrating aid, and the balance is deionized water. Stir at 100-120 r / min for 30-40 min under water bath conditions of 45-60℃.
[0010] S4. Setting: The loaded pulp is formed into paper and then enters the press section. The press line pressure is controlled at 120-140kN / m to remove the moisture of the wet paper web to 55%-65%.
[0011] S5. Drying: The pressed wet paper web is sent to a drying cylinder for drying, using a two-stage gradient drying process. The first stage: the temperature is controlled at 110-130℃, and the second stage: the temperature is controlled at 75-85℃, so that the final moisture content of the paper web is 5.5%-7.5%.
[0012] S6. Calendering: The dried paper web is subjected to soft calendering treatment. The temperature of the calendering roller is 60-70℃ and the linear pressure is 50-60N / cm to produce paperboard.
[0013] By adopting the above technical solution, a specific ratio of antifreeze impregnation solution is added to the pulp after beating. Under warm conditions, osmotic pressure and capillary action are used to allow soluble inorganic salts and small molecule antifreeze protectants to penetrate into the cell cavities and intercellular spaces of plant fibers. This lowers the freezing point of pore water and inhibits ice nucleus formation, reducing the damage to the fiber hydrogen bond network caused by the crystallization expansion of free and bound water under cryogenic conditions. At the same time, the small molecule antifreeze protectant and the water that penetrates into the cell wall play a certain role in internal plasticization, alleviating the freezing embrittlement of cellulose macromolecular chain segments at low temperatures, so that the paperboard still maintains excellent flexibility under cryogenic conditions.
[0014] After gelatinization, cationic starch is added to the slurry before the antifreeze impregnation liquid. This forms a positively charged adsorption layer on the fiber surface and enhances the hydrogen bonding between fibers. This compensates for the loss of interfiber bonding force caused by the deep cold and low humidity environment, so that the paperboard still has high burst strength in the deep cold environment and meets the load-bearing requirements of cold chain stacking.
[0015] A two-stage gradient drying process is adopted. The first stage is high temperature to quickly remove free water, and the second stage is low temperature to slowly dry. This allows the paper to be dehydrated gradually from the inside out, reducing the migration of soluble inorganic salts and small molecule antifreeze agents in the antifreeze impregnation solution to the paper surface and precipitation.
[0016] Preferably, in step S3, the antifreeze wetting solution is added in two parts. The first part is 60%-70% of the total amount of antifreeze wetting solution, and the mixture is stirred for 15-20 minutes at a speed of 100-120 r / min under a water bath at 45-60°C. The second part is the remaining antifreeze wetting solution, and the mixture is stirred for another 15-20 minutes.
[0017] By adopting the above technical solution, the antifreeze impregnation solution is added to the slurry in two stages. The first addition causes the fiber cell walls and cell cavities to initially absorb water and swell, forming an osmotic pressure gradient. The second addition of the remaining antifreeze impregnation solution makes the ion concentration and solute distribution in the pores more uniform. This avoids the problems of sudden increase in local osmotic pressure, severe fiber shrinkage, and uneven distribution of antifreeze solute caused by adding a high concentration of salt solution at once. It helps to improve the penetration depth and retention rate of the antifreeze impregnation solution in the fiber micropores.
[0018] Preferably, in step S3, after the first addition of the antifreeze impregnation liquid, the mixture is premixed at a speed of 60-80 r / min for 1-2 min, then the slurry system is evacuated to -0.06 MPa and maintained for 4-6 min, then restored to normal pressure, and stirred at a speed of 100-120 r / min for 15-20 min in a water bath at 45-60℃, then the remaining antifreeze impregnation liquid is added for the second time, and stirring is continued for 15-20 min.
[0019] By adopting the above technical solution, the antifreeze impregnation solution is first premixed at a low speed to initially wet the fiber surface. Then, the slurry system is evacuated to remove the trapped air in the fiber cell cavities and cell wall gaps. Under negative pressure, the first antifreeze impregnation solution is driven to quickly and deeply penetrate into the fiber pores. After restoring normal pressure, stirring continues. When the fiber pores are basically filled with antifreeze impregnation solution and the osmotic pressure tends to be balanced, the remaining antifreeze impregnation solution is added and stirred until uniform, which further improves the penetration depth of the antifreeze solute in the three-dimensional fiber network.
[0020] Preferably, in step S5, the second drying zone is equipped with a mid-wave infrared radiation source with an infrared wavelength range of 2-5 μm and an infrared radiation intensity of 5-8 kW / m². 2 .
[0021] By adopting the above technical solution, mid-wave infrared energy can moderately penetrate the surface of the paper, exciting the molecular vibration of water in the fiber pores, causing water to migrate slowly from the inside of the paper to the surface and evaporate, maintaining good drying efficiency. This avoids the problems of surface dry shell, internal wet core and uneven drying rate that may occur when drying in a low-temperature drying cylinder. It also inhibits the migration of soluble inorganic salts and small molecule antifreeze agents in the antifreeze impregnation solution to the paper surface with capillary flow and crystallization, ensuring that the antifreeze functional components are more uniformly retained in the fiber cell cavities and intercellular spaces, thereby continuously exerting the anti-crystallization and antifreeze effect in a deep cryogenic environment.
[0022] Preferably, the soluble inorganic salt is calcium chloride.
[0023] By adopting the above technical solutions, calcium chloride has good solubility and freezing point reduction ability, which can meet the antifreeze requirements of cryogenic environments. Calcium chloride has moderate hygroscopicity, and when combined with a two-stage gradient drying process, it can keep the pore water of the fiber in a supercooled or difficult-to-freeze state, unlike highly hygroscopic salts that cause the finished paperboard to absorb moisture and regain moisture. This balances cryogenic antifreeze performance with room temperature storage stability.
[0024] Preferably, the small molecule antifreeze agent is trehalose.
[0025] By adopting the above technical solution, trehalose molecules contain a rigid non-reducing disaccharide structure formed by two glucose units. This structure can form a strong hydrogen bond network with water molecules in the pore water of fibers through multiple sites, converting some free water into bound water that is not easy to freeze, thus reducing the proportion of freezeable water. At the same time, trehalose can inhibit the formation of homogeneous and heterogeneous ice nuclei in supercooled solutions and prevent the recrystallization of existing micro-ice crystals during temperature fluctuations, thereby avoiding the formation of large-sized destructive ice crystals. When used in conjunction with calcium chloride, calcium chloride lowers the freezing point of pore water, while trehalose inhibits ice nucleus formation and ice crystal growth. The two produce a complementary and synergistic effect, allowing the cardboard to maintain the integrity of the fiber network and good flexibility even in a deep cold environment.
[0026] Preferably, the antifreeze impregnation solution further includes 0.2%-0.3% nano-silica, which is ultrasonically dispersed with a portion of deionized water before being added to the antifreeze impregnation solution.
[0027] By adopting the above technical solution, ultrasonic dispersion can break up the agglomeration of nanoparticles, so that they form a stable suspension dispersion system in the slurry, avoiding the agglomeration of nanoparticles in a high ionic strength environment. After nano-silica enters the cell lumen and cell wall gap, it uses the confinement effect of nanopores to divide the pore water into tiny regions smaller than the critical ice nucleus, inhibiting the formation of ice nuclei and the growth of ice crystals. At the same time, the hydroxyl groups on the surface of nanoparticles form a complex hydrogen bond network with cellulose, trehalose and water molecules, further reducing the proportion of freezeable water.
[0028] Preferably, the antifreeze impregnation solution further includes 0.05%-0.1% sodium carboxymethyl cellulose, which is stirred with the antifreeze impregnation solution at 40-50°C until completely dissolved, and then ultrasonically dispersed nano-silica is added.
[0029] By adopting the above technical solution, on the one hand, the sodium carboxymethyl cellulose polymer chain can inhibit the aggregation of nano-silica in an electrolyte environment containing high concentrations of calcium chloride through electrostatic repulsion and steric hindrance, so that the nanoparticles are uniformly dispersed in the fiber pores and give full play to the confinement and crystal-inhibiting effect. On the other hand, sodium carboxymethyl cellulose adsorbs on the fiber surface and in the aqueous phase of the pores, inhibiting ice recrystallization and preventing small ice crystals from merging into large-sized destructive ice crystals under cryogenic conditions and temperature fluctuations. Moreover, the thickening effect of sodium carboxymethyl cellulose can reduce the loss rate of antifreeze solutes during pressing and drying, so that more calcium chloride and trehalose are retained in the fiber cell lumen and intercellular space.
[0030] In summary, this application has the following beneficial effects:
[0031] 1. This application adds an antifreeze impregnation solution to the pulp after beating, and uses osmotic pressure and capillary action to allow the antifreeze components to penetrate into the fiber pores, lowering the freezing point of pore water and inhibiting ice nucleation. Combined with the internal plasticizing effect of small molecule antifreeze protectants, it alleviates fiber embrittlement in deep cold environments. At the same time, cationic starch is added before the antifreeze solution to compensate for the loss of fiber bonding force at low temperatures. Combined with a two-stage gradient drying process to inhibit solute precipitation, the paperboard maintains excellent flexibility, burst strength and stacking load-bearing capacity in deep cold environments.
[0032] 2. The antifreeze impregnation solution is added in two stages. The initial swelling creates an osmotic pressure gradient, and the second addition makes the ion concentration and solute distribution in the pores more uniform. This avoids fiber shrinkage and uneven distribution caused by adding a high concentration of salt solution at once, and improves the penetration depth and retention rate of the antifreeze impregnation solution.
[0033] 3. By moderately penetrating the surface of the paper with mid-wave infrared energy, the molecular vibration of water in the fiber pores is stimulated, and the paper dries gently from the inside out, avoiding surface dryness and uneven drying. This inhibits the precipitation of antifreeze solutes with capillary flow, ensuring that they are uniformly retained inside the fiber and continue to exert their anti-crystallization effect. Detailed Implementation
[0034] The present application will be further described in detail below with reference to the embodiments.
[0035] information cationic starch Quaternary ammonium cationic starch Softwood pulp Bleached sulfate softwood pulp hardwood pulp Bleached sulfate hardwood pulp Penetration aid Fatty alcohol polyoxyethylene ether AEO-5 Nano silica Vaporized silica nanoparticles, particle size 20–30 nm
[0036] Unless otherwise specified, all raw materials used in the following embodiments are commercially available.
[0037] Example 1
[0038] This application discloses a manufacturing process for low-temperature resistant paperboard, including the following steps:
[0039] S1. Starch pretreatment: Cationic starch is added to hot water at 70℃, the mass of the hot water is 10 times the mass of the cationic starch, and the mixture is kept in a constant temperature water bath and stirred at 250r / min for 30min to gelatinize the starch, so as to obtain cationic starch paste. The paste is kept warm for later use.
[0040] S2. Pulp modification: Mix softwood pulp and hardwood pulp at a mass ratio of 6:3, dilute with water to a pulp consistency of 3%-4%, and beat to a freeness of 30-40°SR (determined according to GB / T3332-2004). Add cationic starch paste under heat preservation to the pulp and stir at 100 r / min for 10 min. The amount of cationic starch added is 1.5% of the oven-dry pulp mass.
[0041] S3. Fiber Pore Loading: Add antifreeze impregnation solution to the slurry obtained in S2. The amount of antifreeze impregnation solution added is 5 times the weight of the oven-dry slurry. Stir at 100 r / min for 40 min under a water bath at 45℃. The antifreeze impregnation solution includes: 4% soluble inorganic salt, 3% small molecule antifreeze protectant, 0.3% penetrating agent, and the balance is deionized water. When preparing the solution, dissolve the soluble inorganic salt, small molecule antifreeze protectant, and penetrating agent in deionized water respectively and mix them evenly to obtain the antifreeze impregnation solution. Among them, the soluble inorganic salt is calcium chloride and the small molecule antifreeze protectant is trehalose.
[0042] S4. Setting: The loaded pulp is then formed into paper, controlling the basis weight of the paper to 100g / m³. 2 The paper then enters the press section, where the press line pressure is controlled at 120 kN / m to remove 55%-65% of the moisture from the wet paper web.
[0043] S5. Drying: The pressed wet paper web is sent to a drying cylinder for drying, using a two-stage gradient drying process. The first stage is controlled at 110℃, and the second stage is controlled at 75℃, so that the final moisture content of the paper web is 5.5%-7.5%.
[0044] S6. Calendering: The dried paper web is subjected to soft calendering treatment. The calendering roller temperature is 60℃ and the linear pressure is 50N / cm to produce paperboard.
[0045] Example 2
[0046] This application discloses a manufacturing process for low-temperature resistant paperboard, including the following steps:
[0047] S1. Starch pretreatment: Cationic starch is added to hot water at 80℃, the mass of the hot water is 12 times the mass of the cationic starch, and the mixture is kept in a constant temperature water bath and stirred at 350r / min for 15min to gelatinize the starch, so as to obtain cationic starch paste. The paste is kept warm for later use.
[0048] S2. Pulp modification: Mix softwood pulp and hardwood pulp at a mass ratio of 6:4, dilute with water to a pulp consistency of 3%-4%, and beat to a freeness of 30-40°SR (as determined by GB / T3332-2004). Add cationic starch paste under heat preservation to the pulp and stir at 100 r / min for 20 min. The amount of cationic starch added is 2% of the oven-dry pulp mass.
[0049] S3. Fiber Pore Loading: Add antifreeze impregnation solution to the slurry obtained in S2. The amount of antifreeze impregnation solution added is 6 times the weight of the oven-dry slurry. Stir at 120 r / min for 30 min under a water bath at 60℃. The antifreeze impregnation solution includes: 6% soluble inorganic salt, 5% small molecule antifreeze protectant, 0.5% penetrating agent, and the balance is deionized water. When preparing the solution, dissolve the soluble inorganic salt, small molecule antifreeze protectant, and penetrating agent in deionized water respectively and mix them evenly to obtain the antifreeze impregnation solution. Among them, the soluble inorganic salt is calcium chloride and the small molecule antifreeze protectant is trehalose.
[0050] S4. Setting: The loaded pulp is then formed into paper, controlling the basis weight of the paper to 100g / m³. 2 The paper then enters the press section, where the press line pressure is controlled at 140 kN / m to remove 55%-65% of the moisture from the wet paper web.
[0051] S5. Drying: The pressed wet paper web is sent to a drying cylinder for drying, using a two-stage gradient drying process. The first stage is controlled at 130℃, and the second stage is controlled at 85℃, so that the final moisture content of the paper web is 5.5%-7.5%.
[0052] S6. Calendering: The dried paper web is subjected to soft calendering treatment. The calendering roller temperature is 70℃ and the linear pressure is 60N / cm to produce paperboard.
[0053] Example 3
[0054] This application discloses a manufacturing process for low-temperature resistant paperboard, including the following steps:
[0055] S1. Starch pretreatment: Cationic starch is added to hot water at 75℃, the mass of the hot water is 11 times the mass of the cationic starch, and the mixture is kept in a constant temperature water bath and stirred at 300r / min for 25min to obtain cationic starch paste, which is then kept warm for later use.
[0056] S2. Pulp modification: Mix softwood pulp and hardwood pulp at a mass ratio of 6:3, dilute with water to a pulp consistency of 3%-4%, and beat to a freeness of 30-40°SR (determined according to GB / T3332-2004). Add cationic starch paste under heat preservation to the pulp and stir at 100 r / min for 15 min. The amount of cationic starch added is 1.7% of the oven-dry pulp mass.
[0057] S3. Fiber Pore Loading: Add antifreeze impregnation solution to the slurry obtained in S2. The amount of antifreeze impregnation solution added is 5 times the weight of the oven-dry slurry. Stir at 110 r / min for 35 min under a water bath at 55℃. The antifreeze impregnation solution includes: 5% soluble inorganic salt, 4% small molecule antifreeze protectant, 0.4% penetrating agent, and the balance is deionized water. When preparing the solution, dissolve the soluble inorganic salt, small molecule antifreeze protectant, and penetrating agent in deionized water respectively and mix them evenly to obtain the antifreeze impregnation solution. Among them, the soluble inorganic salt is calcium chloride and the small molecule antifreeze protectant is trehalose.
[0058] S4. Setting: The loaded pulp is then formed into paper, controlling the basis weight of the paper to 100g / m³. 2 The paper then enters the press section, where the press line pressure is controlled at 130 kN / m to remove 55%-65% of the moisture from the wet paper web.
[0059] S5. Drying: The pressed wet paper web is sent to a drying cylinder for drying, using a two-stage gradient drying process. The first stage is controlled at 120℃, and the second stage is controlled at 80℃, so that the final moisture content of the paper web is 5.5%-7.5%.
[0060] S6. Calendering: The dried paper web is subjected to soft calendering treatment. The calendering roller temperature is 65℃ and the linear pressure is 55N / cm to produce paperboard.
[0061] Example 4
[0062] The difference from Example 1 is that step S3 is different.
[0063] S3. Fiber porosity loading: Add antifreeze impregnation liquid to the slurry obtained in S2. The amount of antifreeze impregnation liquid added is 5 times the weight of the oven-dry slurry. The antifreeze impregnation liquid is added in two parts. The first part is 60% of the total amount of antifreeze impregnation liquid. Stir at 100 r / min for 20 min under a water bath at 45℃. The second part is the remaining antifreeze impregnation liquid. Continue stirring for 20 min.
[0064] Example 5
[0065] The difference from Example 4 is that step S3 is different.
[0066] S3. Fiber porosity loading: Add antifreeze impregnation liquid to the slurry obtained in S2. The amount of antifreeze impregnation liquid added is 5 times the weight of the oven-dry slurry. The antifreeze impregnation liquid is added in two parts. The first part is 60% of the total amount of antifreeze impregnation liquid. Premix at 60 r / min for 2 min. Then, evacuate the slurry system to -0.06 MPa and maintain it for 4 min. Then restore normal pressure and stir at 100 r / min for 20 min under a water bath at 45℃. Add the remaining antifreeze impregnation liquid for the second time and continue stirring for 20 min.
[0067] Example 6
[0068] The difference from Example 1 is that step S5 is different.
[0069] S5. Drying: The pressed wet paper web is sent to a drying cylinder for drying, using a two-stage gradient drying process. The first stage is controlled at 110℃, and the second stage is controlled at 75℃. A mid-wave infrared radiation source with an infrared wavelength of 2μm and an infrared radiation intensity of 5kW / m² is installed above the second drying zone. 2 This results in a final paper moisture content of 5.5%-7.5%.
[0070] Example 7
[0071] The difference from Example 1 is that the antifreeze impregnation solution also includes 0.2% nano-silica. In preparation, the soluble inorganic salt, small molecule antifreeze protectant and penetrating agent are dissolved in a portion of deionized water, mixed and stirred evenly to obtain a premixed solution. Another portion of deionized water is taken, nano-silica is added, and ultrasonically dispersed at 50°C for 20 minutes to form a nano-silica dispersion. The nano-silica dispersion is added to the premixed solution, and the remaining deionized water is added to the total amount of the formula. The mixture is stirred evenly to obtain the antifreeze impregnation solution.
[0072] Example 8
[0073] The difference from Example 7 is that the antifreeze impregnation solution also includes 0.05% sodium carboxymethyl cellulose. In preparation, sodium carboxymethyl cellulose is added to a portion of deionized water at 50°C and stirred until completely dissolved. Soluble inorganic salts, small molecule antifreeze protectants, and penetration aids are then added and stirred evenly to obtain a premix. Another portion of deionized water is taken, and nano-silica is added. The mixture is ultrasonically dispersed at 50°C for 20 minutes to form a nano-silica dispersion. The nano-silica dispersion is added to the premix, and the remaining deionized water is added to the total amount of the formula. The mixture is stirred evenly to obtain the antifreeze impregnation solution.
[0074] Example 9
[0075] This application discloses a manufacturing process for low-temperature resistant paperboard, including the following steps:
[0076] S1. Starch pretreatment: Cationic starch is added to hot water at 70℃, the mass of the hot water is 10 times the mass of the cationic starch, and the mixture is kept in a constant temperature water bath and stirred at 250r / min for 30min to gelatinize the starch, so as to obtain cationic starch paste. The paste is kept warm for later use.
[0077] S2. Pulp modification: Mix softwood pulp and hardwood pulp at a mass ratio of 6:3, dilute with water to a pulp consistency of 3%-4%, and beat to a freeness of 30-40°SR (determined according to GB / T3332-2004). Add cationic starch paste under heat preservation to the pulp and stir at 100 r / min for 10 min. The amount of cationic starch added is 1.5% of the oven-dry pulp mass.
[0078] S3. Fiber porosity loading: Add antifreeze impregnation liquid to the slurry obtained in S2. The amount of antifreeze impregnation liquid added is 5 times the weight of the oven-dry slurry. The antifreeze impregnation liquid is added in two parts. The first part is 60% of the total amount of antifreeze impregnation liquid. Premix at 60 r / min for 2 min. Then, evacuate the slurry system to -0.06 MPa and maintain it for 4 min. Then restore the pressure to normal and stir at 100 r / min for 20 min under a water bath at 45℃. Add the remaining antifreeze impregnation liquid for the second time and continue stirring for 20 min.
[0079] The antifreeze wetting solution comprises: 4% soluble inorganic salt, 3% small molecule antifreeze protectant, 0.3% penetrating agent, 0.2% nano silica, 0.05% sodium carboxymethyl cellulose, and the balance being deionized water. To prepare the solution, sodium carboxymethyl cellulose is added to a portion of deionized water at 50°C and stirred until completely dissolved. The soluble inorganic salt, small molecule antifreeze protectant, and penetrating agent are then added and stirred until homogeneous to obtain a premix. Separately, a portion of deionized water is taken, and nano silica is added. The mixture is ultrasonically dispersed at 50°C for 20 minutes to form a nano silica dispersion. This nano silica dispersion is added to the premix, and the remaining deionized water is added to the total amount in the formula. The mixture is stirred until homogeneous to obtain the antifreeze wetting solution.
[0080] S4. Setting: The loaded pulp is then formed into paper, controlling the basis weight of the paper to 100g / m³. 2 The paper then enters the press section, where the press line pressure is controlled at 120 kN / m to remove 55%-65% of the moisture from the wet paper web.
[0081] S5. Drying: The pressed wet paper web is sent to a drying cylinder for drying, using a two-stage gradient drying process. The first stage is controlled at 110℃, and the second stage is controlled at 75℃. A mid-wave infrared radiation source with an infrared wavelength of 2μm and an infrared radiation intensity of 5kW / m² is installed above the second drying zone. 2 This results in a final paper moisture content of 5.5%-7.5%.
[0082] S6. Calendering: The dried paper web is subjected to soft calendering treatment. The calendering roller temperature is 60℃ and the linear pressure is 50N / cm to produce paperboard.
[0083] Example 10
[0084] This application discloses a manufacturing process for low-temperature resistant paperboard, including the following steps:
[0085] S1. Starch pretreatment: Cationic starch is added to hot water at 80℃, the mass of the hot water is 12 times the mass of the cationic starch, and the mixture is kept in a constant temperature water bath and stirred at 350r / min for 15min to gelatinize the starch, so as to obtain cationic starch paste. The paste is kept warm for later use.
[0086] S2. Pulp modification: Mix softwood pulp and hardwood pulp at a mass ratio of 6:4, dilute with water to a pulp consistency of 3%-4%, and beat to a freeness of 30-40°SR (as determined by GB / T3332-2004). Add cationic starch paste under heat preservation to the pulp and stir at 100 r / min for 20 min. The amount of cationic starch added is 2% of the oven-dry pulp mass.
[0087] S3. Fiber porosity loading: Add antifreeze impregnation liquid to the slurry obtained in S2. The amount of antifreeze impregnation liquid added is 6 times the weight of the oven-dry slurry. The antifreeze impregnation liquid is added in two parts. The first part is 70% of the total amount of antifreeze impregnation liquid. Premix at 80 r / min for 1 min. Then, evacuate the slurry system to -0.06 MPa and maintain it for 6 min. Then restore the pressure to normal and stir at 120 r / min for 15 min under a water bath at 60℃. Add the remaining antifreeze impregnation liquid for the second time and continue stirring for 15 min.
[0088] The antifreeze wetting solution comprises: 6% soluble inorganic salt, 5% small molecule antifreeze protectant, 0.5% penetrating agent, 0.3% nano silica, 0.1% sodium carboxymethyl cellulose, and the balance being deionized water. To prepare the solution, add sodium carboxymethyl cellulose to a portion of deionized water at 50°C and stir until completely dissolved. Then add the soluble inorganic salt, small molecule antifreeze protectant, and penetrating agent, and stir until homogeneous to obtain a premix. Separately, take a portion of deionized water, add nano silica, and ultrasonically disperse it at 50°C for 20 minutes to form a nano silica dispersion. Add the nano silica dispersion to the premix, and add the remaining deionized water to the total amount in the formula. Stir until homogeneous to obtain the antifreeze wetting solution.
[0089] S4. Setting: The loaded pulp is then formed into paper, controlling the basis weight of the paper to 100g / m³. 2The paper then enters the press section, where the press line pressure is controlled at 140 kN / m to remove 55%-65% of the moisture from the wet paper web.
[0090] S5. Drying: The pressed wet paper web is sent to a drying cylinder for drying, using a two-stage gradient drying process. The first stage is controlled at 130℃, and the second stage is controlled at 85℃. A mid-wave infrared radiation source with an infrared wavelength of 5μm and an infrared radiation intensity of 8kW / m2 is set above the second drying zone to achieve a final paper moisture content of 5.5%-7.5%.
[0091] S6. Calendering: The dried paper web is subjected to soft calendering treatment. The calendering roller temperature is 70℃ and the linear pressure is 60N / cm to produce paperboard.
[0092] Example 11
[0093] This application discloses a manufacturing process for low-temperature resistant paperboard, including the following steps:
[0094] S1. Starch pretreatment: Cationic starch is added to hot water at 75℃, the mass of the hot water is 11 times the mass of the cationic starch, and the mixture is kept in a constant temperature water bath and stirred at 300r / min for 25min to obtain cationic starch paste, which is then kept warm for later use.
[0095] S2. Pulp modification: Mix softwood pulp and hardwood pulp at a mass ratio of 6:3, dilute with water to a pulp consistency of 3%-4%, and beat to a freeness of 30-40°SR (determined according to GB / T3332-2004). Add cationic starch paste under heat preservation to the pulp and stir at 100 r / min for 15 min. The amount of cationic starch added is 1.7% of the oven-dry pulp mass.
[0096] S3. Fiber porosity loading: Add antifreeze impregnation liquid to the slurry obtained in S2. The amount of antifreeze impregnation liquid added is 5 times the weight of the oven-dry slurry. The antifreeze impregnation liquid is added in two parts. The first part is 65% of the total amount of antifreeze impregnation liquid. Premix at 70 r / min for 2 min. Then, evacuate the slurry system to -0.06 MPa and maintain it for 5 min. Then restore the pressure to normal and stir at 110 r / min for 17 min under a water bath at 55℃. Add the remaining antifreeze impregnation liquid for the second time and continue stirring for 17 min.
[0097] The antifreeze wetting solution comprises: 5% soluble inorganic salt, 4% small molecule antifreeze protectant, 0.4% penetrating agent, 0.2% nano silica, 0.07% sodium carboxymethyl cellulose, and the balance being deionized water. To prepare the solution, sodium carboxymethyl cellulose is added to a portion of deionized water at 50°C and stirred until completely dissolved. The soluble inorganic salt, small molecule antifreeze protectant, and penetrating agent are then added and stirred until homogeneous to obtain a premix. Separately, a portion of deionized water is taken, and nano silica is added. The mixture is ultrasonically dispersed at 50°C for 20 minutes to form a nano silica dispersion. This nano silica dispersion is added to the premix, and the remaining deionized water is added to the total amount in the formula. The mixture is stirred until homogeneous to obtain the antifreeze wetting solution.
[0098] S4. Setting: The loaded pulp is then formed into paper, controlling the basis weight of the paper to 100g / m³. 2 The paper then enters the press section, where the press line pressure is controlled at 130 kN / m to remove 55%-65% of the moisture from the wet paper web.
[0099] S5. Drying: The pressed wet paper web is sent to a drying cylinder for drying, using a two-stage gradient drying process. The first stage is controlled at 120℃, and the second stage is controlled at 80℃. A mid-wave infrared radiation source with an infrared wavelength of 3μm and an infrared radiation intensity of 6kW / m² is installed above the second drying zone. 2 This results in a final paper moisture content of 5.5%-7.5%.
[0100] S6. Calendering: The dried paper web is subjected to soft calendering treatment. The calendering roller temperature is 65℃ and the linear pressure is 55N / cm to produce paperboard.
[0101] Comparative Example 1
[0102] The difference from Example 1 is that the antifreeze wetting solution is replaced with deionized water.
[0103] Comparative Example 2
[0104] The difference from Example 1 is that step S1 is removed and cationic starch paste is not added in step S2.
[0105] Performance testing
[0106] (1) -40℃ Bending performance: The paperboards obtained in Examples 1-11 and Comparative Examples 1-2 were cut into rectangular samples of 180mm×25mm and conditioned in an environment of 23±2℃ and 50±5% relative humidity for 48h. Then the samples were placed in a low temperature test chamber of -40±2℃ for 24h. After taking them out, the samples were immediately folded 180° around a cylindrical rod with a diameter of 30mm in an environment of -40℃. The number of times the samples were bent to breakage was recorded (or the samples were judged to pass if there were no cracks). Ten samples were measured in parallel in each group and the average value was taken. The test results are shown in Table 1 below.
[0107] (2) Edge crush strength (ECT) retention rate at -40℃: The paperboards obtained in Examples 1-11 and Comparative Examples 1-2 were cut into 25mm×100mm sample strips and conditioned in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 48h. The edge crush strength was measured at room temperature (23℃) and -40±2℃ respectively according to GB / T6546-2021 "Determination of edge crush strength of corrugated paperboard". When testing at -40℃, the sample and fixture must be placed in a low temperature test chamber at -40℃ for 24h in advance. The ECT retention rate was calculated by the following formula: ECT retention rate (%) = ECT(-40℃) / ECT(room temperature) × 100%. Five samples were measured in parallel for each group, and the average value was taken. The test results are shown in Table 1 below.
[0108] Table 1 Performance Test Results
[0109] -40℃ Bending performance / cycle ECT retention rate / % Example 1 5 70 Example 2 5 72 Example 3 6 73 Example 4 8 78 Example 5 10 83 Example 6 7 75 Example 7 9 82 Example 8 11 88 Example 9 ≥12 90 Example 10 ≥12 90 Example 11 ≥12 92 Comparative Example 1 1 48 Comparative Example 2 3 53
[0110] In conclusion, the following conclusions can be drawn:
[0111] 1. As can be seen from Example 1 and Comparative Examples 1-2 and Table 1, adding antifreeze impregnation liquid and cationic starch to the pulp can synergistically improve the low-temperature resistance of paperboard. The reason may be that: after pulping, adding antifreeze impregnation liquid to the pulp allows the antifreeze components to penetrate into the fiber pores through osmotic pressure and capillary action, lowering the freezing point of pore water and inhibiting the formation of ice nuclei. Combined with the internal plasticizing effect of small molecule antifreeze protectant, it alleviates fiber embrittlement in deep cold environments. Cationic starch is added before antifreeze impregnation liquid to compensate for the loss of fiber bonding force at low temperatures, so that the paperboard can still maintain excellent flexibility and stacking load-bearing capacity in deep cold environments.
[0112] 2. As can be seen from Examples 1 and 4 and Table 1, adding the antifreeze impregnation solution in two stages is beneficial to improving the low-temperature resistance of the paperboard. The reason may be that adding the antifreeze impregnation solution to the pulp in two stages allows the fiber cell walls and cell cavities to initially absorb water and swell, forming an osmotic pressure gradient. The second addition of the remaining antifreeze impregnation solution makes the ion concentration and solute distribution in the pores more uniform, avoiding the problems of sudden increase in local osmotic pressure, severe fiber shrinkage, and uneven distribution of antifreeze solute caused by adding a high concentration of salt solution at once. This helps to improve the penetration depth and retention rate of the antifreeze impregnation solution in the fiber micropores, thereby improving the low-temperature resistance of the paperboard.
[0113] 3. Combining Examples 1 and 4-5 with Table 1, it can be seen that vacuuming during the first addition of the antifreeze impregnation liquid is beneficial to improving the low-temperature resistance of the paperboard. The reason may be that: first, low-speed premixing allows the antifreeze impregnation liquid to initially wet the fiber surface, and then vacuuming the pulp system removes the trapped air in the fiber cell cavities and cell wall gaps. Under negative pressure, the first addition of antifreeze impregnation liquid is driven to quickly and deeply penetrate into the fiber pores. After restoring normal pressure, stirring continues until the fiber pores are basically filled with antifreeze impregnation liquid and the osmotic pressure tends to be balanced. Then, the remaining antifreeze impregnation liquid is added and stirred until uniform, which further improves the penetration depth of the antifreeze solute in the three-dimensional fiber network, thereby improving the low-temperature resistance of the paperboard.
[0114] 4. As can be seen from Examples 1 and 6 and Table 1, the use of a two-stage gradient drying process supplemented by mid-wave infrared irradiation in the second stage helps improve the low-temperature resistance of the paperboard. The reason may be that mid-wave infrared energy can moderately penetrate the surface of the paper, exciting the molecular vibration of water in the fiber pores, causing water to migrate slowly from the inside of the paper to the surface and evaporate, maintaining good drying efficiency. This avoids the problems of surface dry shell, internal wet core and uneven drying rate that may occur when drying in a low-temperature drying cylinder alone. It also inhibits the migration of soluble inorganic salts and small molecule antifreeze agents in the antifreeze impregnation solution to the paper surface by capillary flow and crystallization, ensuring that the antifreeze functional components are more uniformly retained in the fiber cell cavities and cell wall gaps, thereby helping to improve the low-temperature resistance of the paperboard.
[0115] 5. As can be seen from Examples 1 and 7 and Table 1, adding nano-silica to the antifreeze impregnation solution can improve the low-temperature resistance of the paperboard. The reason may be that after nano-silica enters the cell lumen and intercellular space of the fiber, it uses the confinement effect of nanopores to divide the pore water into tiny regions smaller than the critical ice nucleus, inhibiting the formation of ice nuclei and the growth of ice crystals. At the same time, the hydroxyl groups on the surface of the nanoparticles form a complex hydrogen bond network with cellulose, trehalose and water molecules, further reducing the proportion of freezeable water, thereby improving the low-temperature resistance of the paperboard.
[0116] 6. Combining Examples 1 and 7-8 with Table 1, it can be seen that adding sodium carboxymethyl cellulose to the antifreeze impregnation solution can improve the low-temperature resistance of the paperboard. The reasons may be as follows: On the one hand, the sodium carboxymethyl cellulose polymer chain can inhibit the aggregation of nano-silica in an electrolyte environment containing high concentrations of calcium chloride through electrostatic repulsion and steric hindrance, so that the nanoparticles are uniformly dispersed in the fiber pores and give full play to the confinement and crystal-inhibiting effect. On the other hand, sodium carboxymethyl cellulose is adsorbed on the fiber surface and in the pore aqueous phase, inhibiting ice recrystallization and preventing small ice crystals from merging into large destructive ice crystals under cryogenic conditions and temperature fluctuations. In addition, the thickening effect of sodium carboxymethyl cellulose can reduce the loss rate of antifreeze solutes during pressing and drying, so that more calcium chloride and trehalose are retained in the fiber cell lumen and cell wall gaps, synergistically improving the low-temperature resistance of the paperboard.
[0117] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A production process for low-temperature resistant paperboard, characterized in that, Includes the following steps: S1. Starch pretreatment: Add cationic starch to hot water at 70-80℃, where the mass of the hot water is 10-12 times the mass of the cationic starch. Heat the water in a constant temperature water bath and stir at 250-350 r / min for 15-30 min to gelatinize the starch and obtain a cationic starch paste. Keep the paste warm for later use. S2. Pulp modification: Mix softwood pulp and hardwood pulp at a mass ratio of 6:(3-4), dilute with water to a pulp consistency of 3%-4%, beat the pulp to a freeness of 30-40°SR, add cationic starch paste under heat preservation to the pulp, and stir for 10-20 minutes. The amount of cationic starch added is 1.5%-2% of the oven-dry pulp mass. S3. Fiber Pore Loading: Add an antifreeze impregnation solution to the slurry obtained in S2. The amount of antifreeze impregnation solution added is 5-6 times the oven-dry slurry mass. The antifreeze impregnation solution includes: 4%-6% soluble inorganic salt, 3%-5% small molecule antifreeze protectant, 0.3%-0.5% penetrating aid, and the balance being deionized water. Stir at 100-120 r / min for 30-40 min under water bath conditions of 45-60℃. The soluble inorganic salt is calcium chloride, and the small molecule antifreeze protectant is trehalose. S4. Setting: The loaded pulp is formed into paper and then enters the press section. The press line pressure is controlled at 120-140kN / m to remove the moisture of the wet paper web to 55%-65%. S5. Drying: The pressed wet paper web is sent to a drying cylinder for drying, using a two-stage gradient drying process. The first stage: the temperature is controlled at 110-130℃, and the second stage: the temperature is controlled at 75-85℃, so that the final moisture content of the paper web is 5.5%-7.5%. S6. Calendering: The dried paper web is subjected to soft calendering treatment. The temperature of the calendering roller is 60-70℃ and the linear pressure is 50-60N / cm to produce paperboard.
2. The production process of low-temperature resistant paperboard according to claim 1, characterized in that: In step S3, the antifreeze wetting solution is added in two parts. The first part is 60%-70% of the total amount of antifreeze wetting solution. The mixture is stirred for 15-20 minutes at a speed of 100-120 r / min under a water bath at 45-60℃. The second part is the remaining antifreeze wetting solution, and the mixture is stirred for another 15-20 minutes.
3. The production process of low-temperature resistant paperboard according to claim 2, characterized in that: In step S3, after the first addition of the antifreeze impregnation liquid, the mixture is premixed at a speed of 60-80 r / min for 1-2 min. Then, the slurry system is evacuated to -0.06 MPa and maintained for 4-6 min. After that, the pressure is restored to normal and the mixture is stirred at a speed of 100-120 r / min for 15-20 min in a water bath at 45-60℃. The remaining antifreeze impregnation liquid is added for the second time, and the mixture is stirred for another 15-20 min.
4. The production process of low-temperature resistant paperboard according to claim 1, characterized in that: In S5, the second drying zone is equipped with a mid-wave infrared radiation source with an infrared wavelength range of 2-5 μm and an infrared radiation intensity of 5-8 kW / m². 2 .
5. The production process of low-temperature resistant paperboard according to claim 1, characterized in that: The antifreeze impregnation solution also includes 0.2%-0.3% nano-silica, which is ultrasonically dispersed with a portion of deionized water before being added to the antifreeze impregnation solution.
6. The production process of low-temperature resistant paperboard according to claim 5, characterized in that: The antifreeze impregnation solution also includes 0.05%-0.1% sodium carboxymethyl cellulose. The sodium carboxymethyl cellulose is stirred with the antifreeze impregnation solution at 40-50°C until completely dissolved, and then ultrasonically dispersed nano-silica is added.
Citation Information
Patent Citations
Method for solving linting and dusting during paperboard printing
CN121344982A
Anti-freezing solution for transportation and storage of solid particles as well as preparation method and application of anti-freezing solution
CN121495547A
